Unpacking the ‘magical’ narrative of Creative Youth policy: Where do teachers belong? - Curran, Ailbhe; Kenny, Ailbhe (Irish Journal of Arts Management and Cultural Policy, 2025)
In recent years, ‘creativity’ and ‘arts-in-education’ have become key features of youth arts policy in Ireland and heavily impact the provision of arts education in schools. Since 2017, the Creative Youth Plan and its Creative Schools programme have become the core mechanism by which this policy focus is translated into primary schools. Although the Creative Youth Plan and the Creative Schools programme have been recently renewed, research on their impact is still emerging and remains limited. This article addresses a gap in the research by presenting a critical discourse analysis of the narratives underpinning this plan and its Creative Schools programme, and how they may impact the positioning of primary teachers. Applying a Foucauldian lens, the researchers draw on Stone’s narrative approach (2012) & Pollitt and Hupe’s theory of ‘magic concepts’ (2011) to deconstruct the dominant policy narrative of the Creative Youth 2017-2022 and Creative Youth 2023-2027 Plan and how it is perpetuated through the Creative Schools programme documents. In doing so, it highlights how narratives embedded within policy can create the conditions for the potential othering of primary teachers through the policy’s programme, guiding its practice on the ground.